Environmental and economic optimization for block cutting of dimension stones in a limestone quarry. (December 2021) - Şirin, Ece; Bonduà, Stefano; Elkarmoty, Mohamed
Abstract: The paper presents the evaluation of quarrying operations as specified by the Eco-Label standards for hard coverings, while it develops the work done by (Elkarmoty et al., 2020a). The economic and environmental optimization of the quarry activities were analysed taking in to account several parameters: production costs, obtainable revenues, waste production, dust and CO2 emissions, water and energy consumption, and the Eco-Label 'natural resource' criteria for hard coverings. For the dust and CO2 emissions, water and energy consumption, the research presents a comparison between a chain saw cutter machine and a diamond wire cutter machine. The research's objective is to evaluate the optimal sustainable engineering and optimization practice in terms of economy and the environment by means of block dimensions and block cutting machinery choices. The research was implemented in a case study of limestone quarry bench in Italy. The highest obtainable recovery ratio was detected as 53%, while the obtainable revenues were found in correlation with the recovery ratio, decreasing with increasing block surface area. However, the lowest production costs were obtained for the block dimension that reflected the lowest recovery ratio, hence, highest waste volume. The dust emissions, energy consumption and carbon footprint of the block cutting operations of the quarry were lower when the diamond wire cutter was used, compared to the chain saw cutter, respectively. For the block cutting of the bench, using blocks with lower surface area were found to have higher recovery ratios than the threshold value which Eco-Label natural resources criteria indicates. The excellence level of the Eco-Label criteria can be obtained in the presented case study only by one block dimension. Each criterion was evaluated in order to find the best practice for the quarry in terms of environment, economy and sustainability. Highlights: Improvement of a recent optimization strategy considering new cutting practices. The effects of block dimensions on a quarry's sustainability level were established. Economic and environmental impacts' comparison of several stone cutting machinery. Evaluation of the Eco-Label hard covering criteria in quarrying activities.